2015
DOI: 10.1002/app.41934
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hydrophilic to superhydrophobic SU8 surfaces

Abstract: In published literature, it is widely reported that the plasma treatment and funtionalization with Octadecyltrichlorosilane (OTS) self-assembled monolayer (SAM) can individually alter the wetting properties of SU8 surface. A combination of the two approaches gives better results and the synergism of the two approaches produces a superhydrophobic SU8 surface, which is presented in this work. We have investigated various composition of plasma for treatment of SU8 surfaces and permuted the treated SU8 surfaces wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…A dependence of fouling on membrane surface roughness has been experimentally and theoretically observed. [6][7][8] These studies focused on randomly rough surfaces, but recent research has found a correlation between fouling resistance and induced regular surface roughness. [9][10][11] Through use of nanoimprint lithography (NIL)-a process by which submicron patterns are transferred from a mold to a resist by means of mechanical deformation-commercial polyethersulfone (PES) UF membranes were imprinted with regular line and groove surface patterns.…”
Section: Introductionmentioning
confidence: 99%
“…A dependence of fouling on membrane surface roughness has been experimentally and theoretically observed. [6][7][8] These studies focused on randomly rough surfaces, but recent research has found a correlation between fouling resistance and induced regular surface roughness. [9][10][11] Through use of nanoimprint lithography (NIL)-a process by which submicron patterns are transferred from a mold to a resist by means of mechanical deformation-commercial polyethersulfone (PES) UF membranes were imprinted with regular line and groove surface patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The oil treatment is an alternative method to enhance the hydrophobicity of the surface to minimise the contact angle hysteresis, and similar results may also be obtained using an enhanced OTS surface with superhydrophobic wetting properties [19]. The actuation of DI water droplets was achieved at a voltage as low as 30 V when a layer of mineral oil with an average thickness of 100 µm covered the device.…”
Section: Droplet Actuationmentioning
confidence: 80%
“…When a dried active surface is immersed under water, air is trapped in the cavities as bubbles due to the small size of the cavity and the hydrophobicity of the SU-8 photoresist (∼90° contact angle 27 ). The diameter of the bubble is the same as that of the cavity and the length is normally shorter than that of the cavity, as shown in the inset of Figure 2 .…”
Section: Methodsmentioning
confidence: 99%